Influence of temperature on optimum viscoelastic absorbers in cubic nonlinear systems - Febbo, Mariano (2014)
Recently, viscoelastic materials have been widely used for vibration control due to their efficacy and flexibility in real engineering problems. Their use as constitutive parts of dynamic vibration absorbers requires the investigation of these materials under different operating situations. In the optimal design of the absorbers, it is essential to know how the dynamical properties of the viscoelastic materials change with temperature. In a previous work, the authors presented a methodology to optimally design a linear viscoelastic dynamic vibration absorber to be attached to a cubic nonlinear single-degree-of-freedom system, in a given temperature. In the present work, a study of how temperature variations affect the optimal design of two viscoelastic absorbers, made of distinct materials (neoprene and butyl rubber), is addressed. The mathematical formulation of the problem is based on the concept of generalized equivalent parameters and the harmonic balance method is employed in the solution stage. A cubic nonlinearity in the primary system is considered and the four parameter fractional derivative model of viscoelastic materials is used. Numerical simulations are performed using a recursive equation, in order to find the new characteristics of the absorbers at different working temperatures. The results show that the answer depends not only on the temperature and the material, but also on the magnitude of the excitation load imposed to the system. For a low magnitude of the excitation load, it is verified that the neoprene absorber is less affected by a temperature variation, in terms of its vibration control capabilities. On the other hand, a large magnitude of the load can significantly affect the performance of both considered devices when the working temperature is different from the design temperature.